2020
DOI: 10.3389/fnagi.2020.597579
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Profile of Mild Cognitive Impairment Due to Dementia With Lewy Bodies—An Updated Review

Abstract: Objective: Dementia with Lewy Bodies (DLB) is the second most common type of neurodegenerative dementia. Yet, the domain-specific cognitive impairment of the mild cognitive impairment (MCI) phase of this disease (DLB-MCI) is still not been established. This article gives an updated review on the neuropsychological profile of DLB-MCI, building on the findings from a previous review.Methods: We performed systematic review and searched five different electronic databases (Scopus, Cochrane, EMBASE, MEDLINE, and Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Neuropsychological impairments in dementia with Lewy bodies (DLB) and AD differ, but few well-controlled comparative studies of sufficient sample size have been done in the MCI stages (see Ciafone, Little, Thomas, & Gallagher, 2020;Hemminghyth, Chwiszczuk, Rongve, & Breitve, 2020 for reviews). In MCI-LB, deficits have been reported predominantly in domains impaired in DLB (i.e., visuospatial function, attention, executive function; Donaghy, Taylor, et al, 2018;Donaghy, O'Brien, & Thomas, 2015) although other studies suggest a broad (Kemp et al, 2017) and heterogeneous (Hemminghyth et al, 2020) range of cognitive deficits.…”
Section: Introductionmentioning
confidence: 98%
“…Neuropsychological impairments in dementia with Lewy bodies (DLB) and AD differ, but few well-controlled comparative studies of sufficient sample size have been done in the MCI stages (see Ciafone, Little, Thomas, & Gallagher, 2020;Hemminghyth, Chwiszczuk, Rongve, & Breitve, 2020 for reviews). In MCI-LB, deficits have been reported predominantly in domains impaired in DLB (i.e., visuospatial function, attention, executive function; Donaghy, Taylor, et al, 2018;Donaghy, O'Brien, & Thomas, 2015) although other studies suggest a broad (Kemp et al, 2017) and heterogeneous (Hemminghyth et al, 2020) range of cognitive deficits.…”
Section: Introductionmentioning
confidence: 98%
“…Impairments in attention are a characteristic finding in DLB, and some previous studies have identified this in MCI-LB patients using Digit Span, TMT part B and Stroop [ 64 , 65 , 66 , 67 ]. These conflicting findings may be due to several reasons, including the fact that previous studies investigated MCI-LB patients that were diagnosed by combining MCI, DLB or PDD criteria [ 65 , 66 ] or by retrospectively assigning a diagnosis depending on the individual’s clinical transition [ 64 ]. These studies also reported higher frequencies of CF, VH and parkinsonism, suggesting a more severe population than tested in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A review of several studies also showed that when caused by prodromal DLB, MCI's neuropsychological profile is mainly characterized by deficits in executive, visuospatial, and attentional functions [19]. Another recent investigation confirmed that patients with MCI-LB, in particular, performed poorly in visuoconstructive and executive functions [17].…”
Section: Neuropsychological Assessment Strategiesmentioning
confidence: 96%